Hydrodynamics of In‐Stream Leaky Barriers for Natural Flood Management - Alzabari, Fawaz; Wilson, Catherine A. M. E.; Ouro, Pablo (Water resources research, 2024)
Leaky barriers are in‐stream natural flood management solutions designed for peak flow attenuation, whose effectiveness is dependent on their design. Flow around leaky barriers (LB) composed of three cylindrical logs were investigated using large‐eddy simulation. The main LB configuration considered vertically aligned logs, with other layouts inclined at 15° ^{°}$, 30° ^{°}$, and 45° ^{°}$ in the upstream and downstream directions. Results reveal that the frontal projected blockage area of the LB leads to an increase in the upstream flow depth, with momentum being redirected toward the bottom gap, creating a primary wall‐jet, whose peak velocity and coherence varied depending on LB design, however, attained a similar decay downstream. The porous LBs allowed for distinct internal flow paths that generated secondary jets, either diverting momentum upwards or downwards depending on the direction of the barrier inclination, impacting main flow features and turbulent characteristics. Turbulent kinetic energy and vertical Reynolds shear stress decreased when the barrier was inclined downstream. In the upstream inclination cases, these showed no significant variation, with magnitudes similar to those in the vertical configuration. Bed shear stress decreased with increasing barrier angle, reducing the risk of local scour and sediment mobilization. The vertical LB achieves the maximum backwater rise at the expense of promoting larger sediment bed mobilization. Structural loads on the logs vary with LB inclination, with drag forces decreasing as barrier angles increase. Hydrodynamic findings, evaluated through five design criteria, show that upstream‐inclined designs, particularly with large barrier angles, exhibit improved relative performance compared to other designs. Key Points Study examines leaky barriers of cylindrical logs with inclined upstream and downstream designs for flood management Barrier layout affects flow dynamics, turbulence, and risk of sediment mobilization Upstream‐inclined designs show enhanced flood management performance